Selection and optimization of lipase production from Aspergillus flavus USM A10 via Solid State Fermentation (SSF) on rice husks and wood dusts as substrates - How, Shiao Pau; Omar, Ibrahim Che (Penerbit Universiti Sains Malaysia, 2004)
Solid state fermentation (SSF) involves the growth of microorganisms on moist solid substrates in the absence of free flowing water. The necessary moisture in SSF exists in a complex form which is absorbed within the solid matrix, and this is considered advantageous for growth because of the possible efficient oxygen transfer process.